FLINT ARTEFACTS OF NORTHERN PONTIC POPULATIONS OF THE EARLY AND MIDDLE BRONZE AGE: 3200 – 1600 BC (BASED ON BURIAL MATERIALS) - Razumov, Serhiy (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2011)
The present study sums up the innovative research of Sergiey M. Razumov dealing with the question of funerary applications of flint artefacts documented in Pontic communities of the forest steppe and steppe tied to the prologue of the Bronze Age (3200-1600 BC), usually identified in the form of a sequence of archaeological cultures (according to Razumov as a Cultural-Historical Community; Yamnaya, Catacomb and Babyno)1. The editors of Baltic-Pontic Studies believe research in this context ought to integrate studies on flint use and manufacture at the turn of the Neolithic and Eneolithic, as well as Early Bronze Age among academic circles in Central-Eastern and Eastern Europe. In this respect it could be said that to date there has been a lack of a complete picture of Pontic traditions of manufacture (technology and style), as well as an anthropological perspective of flint artefact applications. Moreover, it is worth noting that Sergiey M. Razumov’s study finds common ground with the broader cycle of studies on ‘The Baltic drainage basin as a region of reception for the tradition of Early Bronze Age Pontic Cultures’ in which growth has an important influence (see Chapter 7 in particular). The general question of a stage-by-stage summary of these studies shall be the subject of a forthcoming volume of Baltic-Pontic Studies. In closing I would like to sincerely thank Professor Jerzy Libera (Marii Curie- -Skłodowska University) and Dr Janusz Budziszewski (Cardinal Stefan Wyszyński University) for their invaluable assistance in regard to research and publication.